Linkages between the Availability of Basic Services Supporting Urban Settlements and Settlement Land Use (Case Study: Rangkasbitung District, Lebak Regency, Banten Province) - Purba, Sabrina; Hadi, R. Chrisna T.; Pujantiyo, Bambang S. (Indonesian Journal Publisher, 2024)
Rapid urbanization has become a significant global phenomenon, affecting major cities and suburban areas and profoundly impacting urban life. This article explores the correlation between the increase in population as an effect of urbanization and the availability of essential services in Rangkasbitung, which consists of 16 villages. This research aims to determine the impact of the availability of crucial daily services on the amount of residential land use in Rangkasbitung. Essential services are assessed using the 20-minute neighborhood parameter, representing an area designed to provide essential services within a short walk for residents. This research uses a quantitative descriptive methodology with spatial and descriptive statistical analysis. The study is limited to the availability of residential land use, essential services, and public transportation as the three main components in the development of urban residential areas based on the 20-Minute Neighborhood parameter. The 20-minute neighborhood is a city planning concept defined as an area where residents can access most activities necessary for a good life without traveling outside the area. The results indicate that the availability of essential services in an area affects residents' decisions on where to live.